An Investigation of Health and Safety Issues at Highway Construction Sites in Developing Countries - Shah, R. K.; Alqarni, M. (Journal of Advanced College of Engineering and Management, 2018)
Construction activities on highway projects are the key source of safety risks to workers and motorists. Workplace fatalities and injuries have significantly reduced since 1970 after implementation of OSHA (Occupational Safety and Health Administration) regulations. However, ergonomic injuries caused by ergonomic risk factors such as awkward or sustained posture, forceful exertion or stain, contract pressure, exposure to vibration, extreme heat or cold environment have major impact on the productivity and safety on the highway construction sites. The paper focuses on identifying the existing safety practices that aid to prevent ergonomic injuries at the highway construction sites. A comprehensive review of literature reveals that majority of work place injuries and fatality victims are from private employment whereas a very few injuries coming from the state or local government employees from contractors. The primary data was collected using questionnaire survey, interview and observations and the spreadsheet was used to analyse the collected data about the causes of workplace injuries and possible measures. The survey results reveal that the most of the injuries such as musculoskeletal disorders, strain and accidents transpired due to the collision with equipment and vehicle!s related incidents. Dump truck, tippers, motor graders and cars cause the frequently reported workplace injuries. The paper concludes that use of Personal Protective Equipment (PPE), compliance to safety regulations, improving traffic control system and changing the culture of employers and employees are possible safety practices need to be adopted to mitigate the ergonomic workplace injuries in the highway construction projects particularly in the developing and least developed countries.